0557 Diagnostic Visual and Automated Polysomnagraphic REM Sleep Without Atonia Thresholds in Isolated REM Sleep Behavior Disorder 2.0. (25th May 2022) - LaClair-Visonneau, Laurene; Feemster, John; Bibi, Noor; Gossard, Thomas; Jagielski, Jack; Strainis, Emma; Steele, Tyler; Carvalho, Diego; Timm, Paul; Boeve, Bradley; Silber, Michael; McCarter, Stuart; et al.
Abstract: Introduction: Accurate, early diagnosis of isolated rapid eye movement (REM) sleep behavior disorder (iRBD) is crucial given its injury potential and neurological prognosis. We aimed to analyze visual and automated REM sleep without atonia (RSWA) diagnostic thresholds in a current cohort of iRBD patients using submentalis (SM) and individual four limb electromyography (EMG) recordings, including bilateral flexor digitorum superificialis (FDS) and anterior tibialis (AT) during polysomnography. Methods: We analyzed RSWA in 20 iRBD patients and 20 age-sex-AHI matched controls who underwent polysomnography between 2017-2021 for phasic burst durations, phasic, tonic, and "any" muscle activity, and automated REM atonia index (RAI). Group RSWA metrics were analyzed with non-parametric comparisons, logistic regression, and receiver operating characteristic (ROC) curves to determine optimal diagnostic cutoff thresholds for iRBD. Correlation explored associative relationships between RSWA metrics, and principal components analysis (PCA) defined determinants of RSWA metric variance. Results: All mean RSWA metrics were higher in iRBD patients than controls (p<0.05), except for left and bilateral AT phasic density and duration. RSWA(phasic%, AUC; "any"%, AUC) cutoffs were: SM (6.5%, AUC=90.2; 6.5%, AUC=92.5); L FDS (7.3%, AUC=95.8; 7.3%, AUC=95.8%); R FDS (5.4%, AUC=93.5; 5.8%, AUC=93.2%); Bilateral FDS (10.7%, AUC=96; 15.3%, AUC=95.8); L AT (6.7%, AUC=74.5; 6.7%, AUC=74.8%); R AT (4.7%, AUC=76.8; 4.7%, AUC=76.8%); Bilateral AT (7.5%, AUC=77.5; 7.5%, AUC=77.5%), combined SM/FDS (15.0%, AUC=95.5; 15.1%; AUC=95.8), combined SM/AT (16.5%, AUC=85.8; 21.0%; AUC=88.8), tonic (0.5%; AUC=85.9), and RAI (0.90; AUC=91.4). Phasic burst duration cutoffs were: SM=0.7s (AUC=90.2), L FDS=0.5 s (AUC=83.2), R FDS=0.6 (AUC=85.2), L AT=0.3 s (AUC=65.0) and R AT=0.4 s (AUC=77.0). PCA demonstrated that FDS and combined SM/FDS and SM/AT RSWA metrics best explained RSWA variance and differentiated controls from RBD, while SM and AT alone were less explanatory. Conclusion: This study provides evidence for quantitative RSWA diagnostic thresholds applicable in current iRBD populations, and confirms the key importance of FDS to assure accurate iRBD diagnosis. Interestingly, these RSWA diagnostic thresholds are lower than previously determined thresholds, suggesting secular trends toward earlier iRBD detection and heterogeneous disease duration relative to polysomnography acquisition, underscoring the necessity of future large scale prospective, multicenter polysomnographic analyses to determine definitive iRBD diagnostic RSWA thresholds. Support (If Any):